Pengembangan Metode Pembelajaran Ceramah Plus Tanya Jawab dan Tugas (CPTT) pada Materi Meyakini Hari Akhir dan Mengakhiri Kebiasaan Buruk Mata Pelajaran PAI dan Budi Pekerti Kelas IX di SMP Negeri 13 Padang - Faril Wahidi; Wirdati Wirdati (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Learning methods are very important. so that its use has an impact on students including enthusiasm in learning, interaction between educators and students and has an impact on learning outcomes. However, if the methods used in learning tend to use only one method, it has an impact on monotonous learning, lack of interaction and affects student learning outcomes. This study aims to develop a method in the form of formulating methods including lecture methods, question and answer and assignments called the CPTT method in PAI &BP lessons.This research uses the Research and Development (R&D) method with a 4D model (Define, Design, Develop, Disseminate). Research instruments in the form of validation sheets, practicality and effectiveness. The data analysis technique used is descriptive data analysis by describing the validity, practicality and effectiveness of the CPTT method. The results obtained include: (a) The validity of the method is declared very valid, (b) The practicality of the method is stated to be very practical (c) The effectiveness of the method is declared very effective. Based on the findings of this study, it was concluded that this CPTT method is valid, practical and effective.